A proliferation of images: Trends, obstacles, and opportunities for visual literacy. Issue 2 (3rd April 2022) - Statton Thompson, Dana; Beene, Stephanie; Greer, Katie; Wegmann, Mary; Fullmer, Millicent; Murphy, Maggie; Schumacher, Sara; Saulter, Tiffany
Abstract: Visual literacy equips learners with the dispositions to critically create, analyse, use, and share visual information. As one component of a discerning, ethical citizenry, visual literacy has become more essential in a rapidly evolving information ecosystem. Against this backdrop, the current Association of College and Research Libraries Visual Literacy Task Force conducted qualitative research from 2019 to 2021, interviewing visual literacy and information literacy experts to identify emergent trends, challenges, and opportunities shaping visual literacy in the twenty-first century. The findings from this study broaden current understandings of visual literacy and empower learners, educators, and practitioners to critically create, share, evaluate, and use visuals in an ever-changing information landscape.